Epidemiological analysis of outbreaks of Foodborne Diseases (DTAs) in the state of Piauí between the years 2015 to 2019 (Research, Society and Development, 2021)
This study aimed to analyze the epidemiological profile of foodborne disease outbreaks in the state of Piauí between the years 2015 to 2019. Information from the Notifiable Disease Information System (SINAN) database was used. of the TABNET program, using electronic means. As it is a public domain database, made available by the Unified Health System (SUS), there was no need to submit the work to the Ethics and Research Committee (CEP). This is a descriptive, ecological, retrospective study with a quantitative approach to secondary data. The analyzed data regarding the outbreaks of Foodborne Diseases (FDAs) in the state of Piauí, reported between the years 2015 to 2019, showed a large number of underreporting, few laboratory identifications, only 12.5%, consequently making the characterization minimal of the etiological agents and making it impossible to classify the DTAs. In addition, in most cases 78.95%, the food that causes the health problem is ignored, contributing to the lack of knowledge of the origin and preventing actions to control production and makes it difficult to clarify the population about the care they should take in order to reduce the risks.